Accurate performance rating of photovoltaic modules under outdoor test conditions. (1st January 2019) - Hüttl, B.; Gottschalk, L.; Schneider, S.; Pflaum, D.; Schulze, A.
Highlights: We report on the approach self-reference algorithm (SRA) for precise outdoor power determination of PV modules. We introduce the outdoor calibration for approach SRA. The characteristics of modules' relevant electric parameters above irradiance are presented. The precise determination of temperature coefficients of electric parameters under outdoor conditions is shown. Reliable outdoor current-voltage characteristics can be acquired and evaluated due to the correct allocation of test conditions to electric measurements by SRA. The expanded uncertainty of power determination, e.g. for STC conditions, is calculated for the measurement chain and the SRA in use. Abstract: Outdoor performance analyses of photovoltaic modules can be advantageous compared to indoor investigations, as they take into account the influences of natural test conditions on the modules. However, such outdoor performance assessments usually suffer from poor accuracies due to undefined test conditions for the modules. This paper reports on a comprehensive concept for improved outdoor analysis which results in performance data with indoor laboratory precision. The approach delivers current-voltage characteristics for even more test conditions than required by the standard IEC 61853-1. Hence, curves of modules' electrical parameters above irradiance can be deduced for any temperatures. The concept allows precise determination of temperature coefficients for user-defined irradiances taking into account outdoor effects like light-soaking or light-induced degradation. The calibration and measurement uncertainty of the presented outdoor analysis method is evaluated quantitatively. For the measurements an advanced outdoor set-up was used.